Herbert Howells’s “Two Afrikaans songs” (1929) - Heinrich van der Mescht (Acta Academica, 2001)
The English composer Herbert Howells (1892-1983) did not understand the Afrikaans language, but he did hear it spoken when he travelled in South Africa in 1921. In his letters from South Africa he made very negative comments on the sound of the language. In this article his “Two Afrikaans Songs” of 1929 (Eensaamheid and Vryheidsgees, on texts by Jan F E Celliers) are analysed in order to determine whether his settings in a language foreign to him are convincing. It is concluded that the songs reveal remarkable sensitivity to the Afrikaans texts. Howells probably consulted the Afrikaans-speaking South African mezzo-soprano Betsy de la Porte, who was a student at the Royal College of Music in London where he was teaching. The “Two  Afrikaans Songs” are a surprising, extraordinary and invaluable contribution to the Afrikaans song repertoire.